Multiple QTL influence the serum Lp(a) concentration: a genome-wide linkage screen in the PROCARDIS study. - Barlera, S; Specchia, C; Farrall, M; Chiodini, B; Franzosi, MG; Rust, S; Green, F; Nicolis, E; Peden, J; Assmann, G; Collins, R; Hamsten, A; et al. (2007)
The serum concentration of lipoprotein Lp (a) is known to be highly heritable and associated with cardiovascular risk. A genome-wide variance component linkage analysis was performed to localise quantitative trait loci (QTLs) influencing Lp(a) levels in a large cohort collected in the PROCARDIS coronary heart disease study. Highly significant linkage was detected at the previously described LP(a) locus on chromosome 6q27 (LOD 108). Taking into account the effect of the locus detected on chromosome 6, a highly significant LOD score was detected on chromosome 13q22-31 (LOD 7.0). Another significant region of linkage was observed on chromosomes 11p14-15 (LOD 3.5). The significant peak at 13q22-31 shows an essential overlap with a locus modulating cholesterol in familial hypercholesterolemia. If the gene underlying these loci is the same, it will be a promising candidate target for manipulating LDL-cholesterol and Lp(a). We also detected linkage at a previously identified locus influencing Lp(a) on chromosome 1q23 (LOD 1.5). Our findings provide new and confirmatory information about genomic regions involved in the quantitative variation of Lp(a) and serve as a basis for further studies of candidate genes in these regions.